Zirconia nanopowder synthesis via detonation of trinitrotoluene. Issue 17 (1st December 2020) - Gibot, Pierre; Vidal, Loic; Laffont, Lydia; Mory, Julien
Abstract: Zirconium (IV) oxide nanopowder was successfully synthesized through the detonation of a mixture composed of 2, 4, 6 trinitrotoluene (TNT, C7 H5 N3 O6 ) and zirconium sulfate tetrahydrate (Zr(SO4 )2 ·4H2 O) as the energetic material and ceramic precursor, respectively. TNT, one of the most popular explosives, is a secondary energetic molecule and exhibits high stability and low sensitivity toward external stresses, making its handling safe. After detonation of the energetic material/ceramic precursor mixture and purification of the detonation soot, a crystallized zirconium oxide (ZrO2 ) powder composed of nanosized particles with a spherical morphology was produced and analysed by the usual characterization techniques (X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy and nitrogen physisorption). The reaction mechanism, considering the thermochemical aspect of the explosive, is offered. This approach could provide promising opportunities for the synthesis of various nano-sized oxide ceramic powders.